Evaluation of Technology Policy Programmes in Germany
X, 363 p.
Keywords: The evaluation of government programmes and measures in the field of technology policy has gained in significance in Germany over the past decade. A variety of evaluation studies on individual projects or programmes with different aims, approaches and methods are available. Which experiences were gained with the instrument of evaluation in this policy area? Evaluation of Technology Policy Programmes in Germany: demonstrates trends of government policy in Germany; documents experiences with the use of various promotion instruments; represents approaches and methods, used in the past years to test the efficiency of various tools of industrial technology policy and discusses their strengths and weaknesses, and draws conclusions for the further development of the evaluation of technology policy in selected areas. £/LIST£ The book includes contributions by authors from the most highly recognized German institutes and consultants working in the evaluation of technology policy, of interest to policy makers, administrators, as well as researchers, scholars and students of economics, innovation research and public policy.